Formulácia opiátových liekových foriem odolných voči zneužívaniu - Husár, Štefan; Sýkorová, Miroslava; Rumlová, Katarína; Chomaničová, Kamila; Vladovičová, Beáta; Bednárová, Adriana (Chemické listy, 2020)
Prescription opioid abuse is a worldwide growing significant health problem. For that reason, the manufacturing of abuse-deterrent dosage forms is highly important. Alcohol is likely to interact with the drug product and causes a sudden drug liberation (i.e., dose dumping), which possibly results in dangerous side effects and poses a serious safety concern. Thus, it is necessary to develop robust dosage forms that are resistant to the effects of various ethanol concentrations in order to eliminate the risk of immediate release of the entire opioid dose. In this article we review the current information available for drug products and existing formulation strategies that prevent both drug abuse and ethanol-induced dose dumping. These studies may provide insight into how various technologies may differ in their ability to deter opiate drugs abuse.
Keywords: lékové formy; Analgesics, Opioid; Dosage Forms; Drug Misuse; Humans; zneužívání léčiv; lidé; Drug Liberation; opioidní analgetika; uvolňování léčiv